PENGARUH LAMA PENYIMPANAN TERHADAP KADAR AIR KUALITAS FISIK DAN SEBARAN JAMUR WAFER LIMBAH SAYURAN DAN UMBI-UMBIAN - Solihin ,; Muhtarudin ,; Rudy Sutrisna (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2015)
This research aims to understanded the effect of a long storage on water content, physical qualities (color, scent, and texture), and fungus scatters on the wafers of vegetables and potatoes waste. The composition of the wafers (%DM): squashs 3,68 %, green mustards 7,81 %, carrots 33,28 %, tomatoes 2,74 %, sweet potatoes 29,77 %, potatoes 5,38 %, cauliflowes leaves 5,91 %, molasses 11,38 %, and salt 0,05 %. This study was conducted in September 2014—October 2014 at Bandar Baru, Sukau, West Lampung and analysed at Laboratory of Nutrition and Feedstuffs, Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. The design of treatment used Completely Random Design (CRD) with three treatments and four tests and then continued with Least Significant Difference Test (LSDT). This research result indicated that long storage had significantly effect (P<0,01) on the water content, physical qualities, and fungus scatters on the wafers of vegetables and potatoes waste. The lowest water content, solid texture, brownish color, the scent of typical wafers and there was no a growth of fungus on wafers vegetables and potatoes waste can still could be still maintained until the fourth weeks.